Accessory Chromosome-Acquired Secondary Metabolism in Plant Pathogenic Fungi: The Evolution of Biotrophs Into Host-Specific Pathogens - Witte, Thomas E.; Villeneuve, Nicolas; Boddy, Christopher N.; Overy, David P. (Frontiers in Microbiology, 2021)
Accessory chromosomes are strain- or pathotype-specific chromosomes that exist in addition to the core chromosomes of a species and are generally not considered essential to the survival of the organism. Among pathogenic fungal species, accessory chromosomes harbor pathogenicity or virulence factor genes, several of which are known to encode for secondary metabolites that are involved in plant tissue invasion. Accessory chromosomes are of particular interest due to their capacity for horizontal transfer between strains and their dynamic ‘crosstalk’ with core chromosomes. This review focuses exclusively on secondary metabolism (including mycotoxin biosynthesis) associated with accessory chromosomes in filamentous fungi and the role accessory chromosomes play in the evolution of secondary metabolite gene clusters. Untargeted metabolomics profiling in conjunction with genome sequencing provides an effective means of linking secondary metabolite products with their respective biosynthetic gene clusters that reside on accessory chromosomes. While the majority of literature describing accessory chromosome-associated toxin biosynthesis comes from studies of Alternaria pathotypes, the recent discovery of accessory chromosome-associated biosynthetic genes in Fusarium species offer fresh insights into the evolution of biosynthetic enzymes such as non-ribosomal peptide synthetases (NRPSs), polyketide synthases (PKSs) and regulatory mechanisms governing their expression.